Implementation of a Hospital Management System in Maintaining Google Customer Review Rating Performance Using the Servqual Method - Irawan Irawan; Andiko Nugraha Kusuma; Mukhlasin Mukhlasin; Edna Maryani; Oktioza Pratama (Universitas Ibn Khladun Bogor, 2026)
This study aims to analyze service quality at Citra Sundari Hospital by comparing patients’ expectations and perceptions using the SERVQUAL method. The research employed a descriptive quantitative approach using a questionnaire consisting of 24 statements (P1–P24) covering the dimensions of tangible, reliability, responsiveness, assurance, and empathy. Data were analyzed using SPSS to obtain descriptive statistics and gap values between expectation and perception variables. The results showed that the average expectation scores ranged from 3.80 to 3.93, while the perception scores ranged from 3.66 to 3.90. Most indicators showed negative gaps, indicating that the services received by patients had not fully met their expectations, although overall service quality was categorized as good. The largest gaps were found in indicators P8 and P23 with a value of -0.20, while indicators P11 and P12 showed positive gaps. These findings indicate the need for service quality improvement, particularly in aspects with the largest gaps, in order to optimize patient satisfaction.